Evaluation of 11C-BU99008, a positron emission tomography ligand for the Imidazoline2 binding site in human brain - Tyacke,R; Myers,J; Venkataraman,A; Mick,I; Turton,S; Passchier,J; Husbands,S; Rabiner,EA; Gunn,R; Murphy,P; Parker,C; Nutt,D (Journal of Nuclear Medicine, 2018)
The imidazoline2 binding sites (I2BS), are thought to be expressed in glia, and implicated in the regulation of glial fibrillary acidic protein. A positron emission tomography (PET) ligand for this target would be important for the investigation of neurodegenerative and neuroinflammatory diseases. 11C BU99008 has previously been identified as a putative PET radioligand. Here we present the first in vivo characterisation of this PET radioligand in humans and assess its test-retest reproducibility. Methods: 14 healthy male volunteers underwent dynamic PET imaging with 11C BU99008 and arterial sampling. Six subjects were used to assess test-retest and eight were used in the pharmacological evaluation, undergoing a second, or third heterologous competition scan with the mixed I2BS/α2 adrenoceptor drug, idazoxan (n=8; 20, 40, 60 and 80 mg) and the mixed irreversible monoamine oxidase (MAO) A/B inhibitor, isocarboxazid (n=4; 50 mg), respectively. Regional time-activity data were generated from arterial plasma input functions corrected for metabolites using the most appropriate model to derive the outcome measure VT (regional total distribution volume). All image processing and kinetic analysis was performed in MIAKAT™ (www.miakat.org). Results: Brain uptake of 11C BU99008 was good with reversible kinetics and a heterogeneous distribution consistent with known I2BS expression. Model selection criteria indicated that the 2-tissue-compartment was preferred. VT estimates were high in the striatum (105±21 mL cm 3), medium in cingulate cortex (62±10 mL cm 3) and low in the cerebellum (41±7 mL cm 3). Test-retest reliability was found to be reasonable. The uptake was dose-dependently reduced by pre-treatment with idazoxan throughout the brain, with an average block across all regions of ~60% (VT≅30 mL cm 3) at the highest dose (80 mg). The median effective dose (ED50) for idazoxan was calculated as 28 mg. Uptake was not blocked by pre-treatme